1999
DOI: 10.1007/s004150050346
|View full text |Cite
|
Sign up to set email alerts
|

Daytime somnolence in myotonic dystrophy

Abstract: Somnolence in myotonic dystrophy (DM) has not been measured using a reliable daytime somnolence scale. The aim of this study was to compare somnolence in DM patients with healthy controls and Charcot-Marie-Tooth disease (CMT) patients using such a scale and to compare this with potential contributory factors. We investigated 35 subjects with adult-onset DM, 16 healthy controls and 13 CMT controls. The Epworth Sleepiness Scale (ESS) was the principal measurement of daytime somnolence. Nocturnal sleep was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 40 publications
7
60
1
Order By: Relevance
“…Among these symptoms, EDS, which is a very characteristic symptom of sleep apnea, is very common in MD [13][14][15][16][17][18]. Guilleminault et al found a correlation in MD patients between EDS and apnea index [3].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among these symptoms, EDS, which is a very characteristic symptom of sleep apnea, is very common in MD [13][14][15][16][17][18]. Guilleminault et al found a correlation in MD patients between EDS and apnea index [3].…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, PSG should always be considered in the presence of this symptom. EDS is common also in patients with MD [13][14][15][16][17][18]. Published sleep studies in MD patients with EDS have reported that sleep apnea is the most common cause of this symptom in MD [15,16,19,20].…”
Section: Introductionmentioning
confidence: 96%
“…Excessive daytime sleepiness is a prominent complaint made by partners and relatives of patients with DM1, 55,90,102 but the patients seem to minimize the problem for unclear reasons that may relate to their global cognitive and behavioral profile. This attitude may explain why the Epworth Sleep Scale often underestimates excessive daytime sleepiness in patients with DM1.…”
Section: Global Intelligencementioning
confidence: 98%
“…27,41 Adult-Onset DM1. More than 50% of patients with classic DM1 are referred because of excessive daytime sleepiness 55,90,102 or fatigue. 49 Patients usually minimize their symptoms, do not keep outpatient appointments, and seem unconcerned about their health.…”
Section: Evidence For Brain Involvement In Dm1mentioning
confidence: 99%
“…The second group of myotonic disorders consists of the dominantly inherited multisystem myotonic dystrophies [2•,31,32]. Myotonic dystrophy type 1 (Steinert's disease) is the most common muscular dystrophy of adult life characterized by myotonia, endocrine dysfunctions, cataract formation, cardiac conduction defect, and muscle weakness [33,34]. Hypersomnolence, hypercapnia, SDB, and nocturnal desaturation are common in myotonic dystrophy.…”
Section: Muscle Fiber Diseasementioning
confidence: 99%